2006
DOI: 10.1080/00071660600732353
|View full text |Cite
|
Sign up to set email alerts
|

Phytase effects on the efficiency of utilisation and blood concentrations of phosphorus and calcium in Pekin ducks

Abstract: The objective was to study the effects of a supplementation of a 6-phytase 1 derived from the Peniophora lycii gene in the White Pekin duck. 2. In two balance studies, low-phosphorus (P) diets consisting mainly of maize, solvent 3 extracted soybean meal and solvent extracted sunflower meal were supplemented with 4 phytase up to concentrations of 1500 U/kg (Study 1) or 2000 U/kg (Study 2). Each diet 5 (phytase level) was fed to 8-10 individually penned ducks. The intake and excretion of each 6 animal was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Likewise, FI of ducks on diets containing 500, 1,000, or 1,500 units of phytase per kilogram of diet increased by 6, 34, or 35%, respectively, relative to the NC diet. In a variety of studies, similar improvements in growth performance of ducks (Orban et al, 1999;Rodehutscord et al, 2003Rodehutscord et al, , 2006 or broiler chicks (Adedokun et al, 2004;Dilger et al, 2004;Pirgozliev et al, 2008) when low-P diets are supplemented with inorganic P or phytase have been reported.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Likewise, FI of ducks on diets containing 500, 1,000, or 1,500 units of phytase per kilogram of diet increased by 6, 34, or 35%, respectively, relative to the NC diet. In a variety of studies, similar improvements in growth performance of ducks (Orban et al, 1999;Rodehutscord et al, 2003Rodehutscord et al, , 2006 or broiler chicks (Adedokun et al, 2004;Dilger et al, 2004;Pirgozliev et al, 2008) when low-P diets are supplemented with inorganic P or phytase have been reported.…”
Section: Discussionmentioning
confidence: 82%
“…Linear regression equations for the different dependent and independent variables for ducks fed a low-P negative control diet supplemented with graded levels of inorganic P or phytase from d 7 to 17 posthatch and calculated P equivalency values (g/kg of diet) of phytase al., 2009). In particular, improvement in P retention when phytase is added to low-P diets is well documented (Broz et al, 1994;Viveros et al, 2002;Rodehutscord et al, 2006) and is the main reason for supplementing the diets of nonruminant animals with phytase. The NC diet and those supplemented with inorganic P or phytase were formulated to contain similar Ca concentrations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1 and 2 by Rush et al (2005). In two balance studies conducted by Rodehutscord et al (2006) this ratio was 1.6:1 and 1.9:1. In two balance studies conducted by Rodehutscord et al (2006) this ratio was 1.6:1 and 1.9:1.…”
Section: Phosphorus Accretion and P Concentration In Body Weight Gainmentioning
confidence: 87%
“…Farrell et al (1993) supplemented duckling diets at 4.1 to 5.3 g total P/kg with 850 U/kg Aspergillus niger phytase and found an increase in P utilisation from 35 to 49% in 2 to 10 d old ducks and from 52 to 59% in 10 to 17 d old ducks. Phytase from Aspergillus niger and Peniophora lycii caused a nonlinear increase in the aP content of duck diets when supplemented in a range between 150 and up to 2,000 U/kg Rodehutscord et al, 2006). Phytase improved precaecal P digestibility and tibia ash content in some studies, but growth was not always positively effected, depending on the level of P supply and age (Martin et al, 1998;Orban et al, 1999;Attia, 2003).…”
Section: Phytase Efficacymentioning
confidence: 97%